Technological Marks on Pot Bases fromChalcolithic Gülpınar - Özdemir, Abdulkadir; Özdemir, Ayşe (My University, 2021)
This essay aims to examine the technological marks observed on the pot bases from the Chalcolithic site of Gülpınar in northwestern Anatolia. These technological marks, which are mainly related to stage of the forming of the pots, represents the negative impressions of mats, baskets, cloth, and tree leaves, as well as finger prints. These negative impressions on pot bases are characteristic of both Early Chalcolithic (phase II) and Middle Chalcolithic period (phase III) at Gülpınar and they appear almost on pot bases recovered from the site during excavations. Examination of these technological marks in the shape of negative impressions on pot bases from Gülpınar help us to obtain information on the techniques used to make the woollen cloth, mats, and baskets and what kind of raw materials were used in their production. The negative impressions of mats, baskets, cloth, or tree leaves on pot bases result from their use as primitive turntables.
Keywords: Arkeoloji